Ultrasound-Guided Thyroid Biopsy - Chintapalli, Ravi Theja V.; Harmath, Carla B. (Seminars in Interventional Radiology, 2024)
Thyroid nodules are prevalent, estimated to affect up to 68% of the population, and the incidence increases with age. With the advances in medical imaging utilization, the detection of incidental thyroid nodules continues to rise, and given the low rate of malignancy in incidentally discovered thyroid nodules (4–15%), diagnostic guidelines are imperative for their management. Several guidelines have been developed: the most commonly used guidelines in the United States include the American Thyroid Association (ATA) Guidelines and the American College of Radiology Thyroid Imaging Reporting Data System (TI-RADS). These guidelines call for the utilization of a biopsy of nodules depending on a sonographic morphologic categorization. This article aims to briefly review these two main guidelines and discuss the techniques for ultrasound-guided biopsy of thyroid nodules.
Keywords: thyroid nodules; ultrasound-guided biopsy; American Thyroid Association; TI-RADS; interventional radiology